Diagnostic test utilization in evaluation for resective epilepsy surgery in children. Issue 4 (11th February 2014) - Jayakar, Prasanna; Gaillard, William D.; Tripathi, Manjari; Libenson, Mark H.; Mathern, Gary W.; Cross, J. Helen; ,
Summary Epilepsy surgery is highly successful in achieving seizure freedom in carefully selected children with drug‐resistant focal epilepsy. Advances in technology have aided presurgical evaluation and increased the number of possible candidates. Many of the tests employed are resource intense, and in specific cases they may be unhelpful or have adverse effects. Some standardization of the evaluation process is thus considered timely. Given the lack of class 1 or 2 evidence defining the relative utility of each test in specific clinicopathologic cohorts, a set of expert recommendations was attempted using consensus among members of the Pediatric Epilepsy Surgery Task Force of the International League Against Epilepsy (ILAE) Commissions of Pediatrics and Diagnostics These recommendations aim to limit fringe over or underutilization of use while retaining substantial flexibility in the use of various tests, in keeping with most standard practices at established pediatric epilepsy centers. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.